2010
DOI: 10.1007/s00428-010-1017-2
|View full text |Cite
|
Sign up to set email alerts
|

Different immunohistochemical and ultrastructural phenotypes of squamous differentiation in bladder cancer

Abstract: Besides worse prognosis of bladder cancer with squamous differentiation (pure squamous cell carcinoma (SCC) or mixed urothelial carcinoma (UC/SCC)), high-grade non-keratinising squamous differentiation is difficult to identify in haematoxylin-eosin stainings. This study aims to validate routine immunohistochemical markers for squamous differentiation in a larger cohort of patients. Tissue microarrays of 89 pure SCCs and mixed UC/SCCs, 66 urothelial carcinomas (UC), precursor lesions and normal urothelium were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 19 publications
2
40
0
1
Order By: Relevance
“…Tissue microarrays (TMA) of previously characterized formalin-fixed, paraffin-embedded squamous differentiated bladder cancer specimens were used [25]. The residual TMAs contained 34 cases of pure squamous cell carcinomas (5 pT2, 24 pT3, 5 pT4) and 39 cases with mixed squamous and urothelial differentiation (5 pT2, 31 pT3, 3 pT4).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue microarrays (TMA) of previously characterized formalin-fixed, paraffin-embedded squamous differentiated bladder cancer specimens were used [25]. The residual TMAs contained 34 cases of pure squamous cell carcinomas (5 pT2, 24 pT3, 5 pT4) and 39 cases with mixed squamous and urothelial differentiation (5 pT2, 31 pT3, 3 pT4).…”
Section: Methodsmentioning
confidence: 99%
“…34 In a study that analyzed 48 pure bladder SCCs and 56 mixed (SCC and urothelial carcinoma) tumours, 96% of pure SSCs stained strongly positively for CK5 and CK14 markers and negative for CK20. 67 By comparison, 86–93% of mixed tumours stained strongly positive for CK5 and CK14, negative for uroplakin, and rarely positive for CK20. 67 Another study analyzed 20 micropapillary variants of urothelial carcinomas and demonstrated that these cancers stained positive for both 343E12 (basal cell marker) and CK20.…”
Section: Prognostic Role Of Bladder Cscsmentioning
confidence: 99%
“…These include how its effects on normal urothelial cell and tissue differentiation are mediated, which ligands of the NOTCH receptors are active in the normal urothelium and how they change in cancers, and whether NOTCH1 and NOTCH2 mutations have equivalent consequences. Specifically, Notch signaling deserves closer investigation in the various forms of squamous cell carcinoma of the bladder [10]. Importantly, further studies in larger cohorts are required to evaluate the impact of Notch pathway inactivation on patient prognosis and on response to targeted and conventional chemotherapy in bladder cancer.…”
mentioning
confidence: 99%